Dropwise evaporation of hydrophilic coolant droplets: A methodology for the development of hydrophilic coating and attainment of enhanced heat transfer. (June 2019) - Panda, Anita; Pati, A.R.; Kumar, A.; Mohapatra, S.S.
Abstract: The solid-liquid interfacial behavior and thermo-physical properties of the coolant decides the boiling regime of the single and multi-droplet evaporative cooling. The alteration of aforesaid phenomenon and parameter in the favorable direction of heat transfer results thermal enhancement in transition boiling regime. The open literature does not disclose the exact methodology for the attainment of above discussed alteration. Therefore, in the current work, an attempt has been made to propose a methodology depicting augmented dropwise evaporation due to simultaneous variation of the interfacial behavior and thermo-physical properties of the coolant. In the current research, by using Polyethylene Glycol (PEG) as an additive, the surface is modified to hydrophilic at very high temperature (up to 400 °C) and the favorable changes of the thermo-physical properties are also attained. The altered variation clearly demonstrates the formation of very high thermally and mechanically stable hydrophilic coating due to adsorption of PEG on the steel plate by quenching effect. Therefore, in addition to the attainment of enhancement at higher temperature, the proposed process also reveals a new route for the development of superhydrophilic coating. The SEM analysis and contact angle measurement on the post heat treated steel confirms the hydrophilicity of the surface during cooling and the FT-IR analysis corroborates the above-mentioned findings. In addition to the above, the droplet lifetime shows a decreasing trend with the increasing PEG concentration and substrate temperature. The droplet impact mapping asserts the transition of Leidenfrost point from 200 °C to above 400 °C. The nature of boiling curve ensures the exclusion of film-boiling regime from the entire cooling process. The critical heat flux is increased up to 0.22 MW/m 2, which is very high in comparison with the literature. The developed coating during solidification of the material can be directly used for the fabrication of gradient surface.